Oral susceptibility of Singapore Aedes (Stegomyia) aegypti (Linnaeus) to Zika virus. - MeiZhi Irene Li; Pei Sze Jeslyn Wong; Lee Ching Ng; Cheong Huat Tan (PLoS Neglected Tropical Diseases, 2012)
Background Zika virus (ZIKV) is a little known flavivirus that caused a major outbreak in 2007, in the South-western Pacific Island of Yap. It causes dengue-like syndromes but with milder symptoms. In Africa, where it was first isolated, ZIKV is mainly transmitted by sylvatic Aedes mosquitoes. The virus has also been isolated from Ae. aegypti and it is considered to be the vector involved in the urban transmission of the virus. Transmission of the virus by an African strain of Ae. aegypti has also been demonstrated under laboratory conditions. The aim of the present study is to describe the oral susceptibility of a Singapore strain of Ae. aegypti to ZIKV, under conditions that simulate local climate. Methodology/principal findings To assess the receptivity of Singapore's Ae. aegypti to the virus, we orally exposed a local mosquito strain to a Ugandan strain of ZIKV. Upon exposure, fully engorged mosquitoes were maintained in an environmental chamber set at 29 °C and 70-75% RH. Eight mosquitoes were then sampled daily from day 1 to day 7, and subsequently on days 10 and 14 post exposure (pe). The virus titer of the midgut and salivary glands of each mosquito were determined using a tissue culture infectious dose(50) (TCID(50)) assay. High midgut infection and salivary gland dissemination rates were observed. By day 5 after the infectious blood meal, ZIKV was found in the salivary glands of more than half of the mosquitoes tested (62%); and by day 10, all mosquitoes were potentially infective. Conclusions/significance This study showed that Singapore's urban Ae. aegypti are susceptible and are potentially capable of transmitting ZIKV. The virus could be established in Singapore should it be introduced. Nevertheless, Singapore's current dengue control strategy is applicable to control ZIKV.